A Bibliometric Analysis of Customer Engagement : Evidence From Hospitality Industry - Zulkifli Musannip Efendi Siregar; Deden Rudy Mustafa; Yayuk Yuliana; Guntur Syahputra (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
Customer engagement is one of the most important factors to achieve positive hospitality performance. Several studies related to customer engagement in the hospitality industry have been conducted by several researchers, but research with bibliometric analysis in the hospitality sector is still rare.  This bibliometric analysis research aims to map research trends related to the field of customer engagement in the hospitality sector. Data were collected from the Scopus database, with the keywords"customer engagement" AND hospitality OR hotel", then screening was carried out, namely 2015-2024, document type is article and conferences, language uses English publications. Based on the keywords and criteria that have been determined, the number of publications was 189 publications. Data were analyzed using Vos Viewer software. The results showed that the trend of publications related to customer engagement in the hospitality industry has increased from year to year, and the contribution to the hospitality sector among researchers is increasing. Keyword analysis on the vos viewer shows that customer engagement has 90 occurrences. Based on the density visualization, several variables that are still rarely studied such as sustainability, corporate social responsibility, engagement, self-image congruity, Service experience, customer experience, brand image, value co-creation and customer engagement behavior. This study concludes that empirical research should be conducted in the future, such as corporate responsibility towards sustainability with customer engagement as a mediating or as a moderation, self-image congruity theory on  customer engagement in the hospitality industry, and service experience, customer experience, brand image, value co-creation and customer engagement behavior.